Self-Control and Hedonism: How Generation Z Paylater Users in Bandar Lampung Manage Their Finances - Defanko, Velicia Anindita; Nurhayaty, Any; Zahra, Fatimah (Faculty of Psychology, Universitas Semarang, 2025)
Generation Z is known as the group most familiar with technology, making them more susceptible to using paylater services. Self-control and hedonistic tendencies are assumed to play a role in influencing their financial management behavior. This study aims to examine the relationship between self-control, hedonism, and financial management among paylater users in Bandar Lampung. The research design used was quantitative correlational with 332 participants aged 17–28 years selected through purposive sampling. The results of multiple regression analysis showed that self-control and hedonism had a significant effect on financial management with a significance level of 0.01 < 0.05. Partially, self-control has a strong positive influence (p=0.001) and an effective contribution of 14.9%, while hedonism shows a significant negative influence (p=0.004) and an effective contribution of 5.5%. These findings confirm that self-control is more dominant in shaping healthy financial management behavior than hedonism, which tends to have the opposite effect.